Sierra Leone : Ex Post Assessment of Longer-Term Program Engagement. (IMF Staff Country Reports; Country Report ;, 2010)
The political and security focus has shifted from post-conflict needs to consolidating gains on peace and stability. Macroeconomic stability has been re-established, and debt relief has improved the debt sustainability outlook. This enabled a gradual switch in policy priorities toward creating an enabling environment for sustained growth. Continued attention to capacity-building is needed. The key fiscal objective is to improve revenue collection to create fiscal space for expanding priority spending. The parsimonious use of structural conditionality should continue, and collaboration with budget support donors should be further strengthened.